CÂNCER DE MAMA E ANÁLISE DOS FATORES RELACIONADOS AOS MÉTODOS DE DETECÇÃO E ESTADIAMENTO DA DOENÇA - Cynthia Angelica Ramos de Oliveira Dourado; Cícera Maria Fernandes dos Santos; Vilma Maria de Santana; Thaís Neves Gomes; Laysa Thayane Silva Cavalcante; Morgana Cristina Leôncio de Lima (Cogitare Enfermagem, 2022)
Objective: to describe the profile of women affected by breast cancer and to evaluate the aspects related to the disease detection and staging methods and their associations. Method: a crosssectional study conducted with 350 women diagnosed with breast cancer treated in specialized centers from Pernambuco - Brazil, between June 2018 and January 2019. For the analysis, associations and comparisons were made with the Chi-square test. Results: 40.3% of the sample was <50 years old, and self-examination was the prevalent detection method (74.9%) in all age roups, with a significant association for more advanced stages of the disease, >70% of the sample. Conclusion: detection by self-examination was significant and was related to more advanced stages of breast cancer, especially in younger age groups. Given the results, the actors involved in women’s health may develop new strategies to intensify population screening.